Moral and spiritual aspects in counseling: Recent development in the West - Abdul Mufid (Journal of Advanced Guidance and Counseling, 2020)
This paper aims to explore the moral and spiritual dimensions of counseling. Since professional counseling has developed in the West, the cultural identity and individualistic orientation of identity has entered the counseling profession. Recently a surge of interest in spirituality and religion has been noted with several treatments focused on a new approach to counseling. The new approach shows that spirituality in life is central to individuals, families and communities. Therapists examine the relationship between spirituality and general psychological health. Secular and religious professionals recognize the paradigm shift from illness to health and from individualism to collectivism. Counseling that develops from the premise of such a therapist must be free of value. The emergence of an integrated perspective with religious and spirituality counseling views has resulted in a fundamental conflict with the prevailing professional value system. Counselors still want to avoid the role of a moralist. The controversy also relates to the firmness one wants, the therapist attaching moral and spiritual dimensions while advocating certain values. Psychotherapy, as a moralistic company, requires modification in its training program. Therapists need to change their orientation, namely as scientists with deep moral or spiritual commitment. Clients need and demand reorientation like this. This profession has a claim to respond to the needs of its clients and it cannot ignore the impetus that arises in practice.Studi literatur ini bertujuan untuk mengeksplorasi dimensi moral dan spiritual dalam konseling. Sejak konseling profesional berkembang di Barat, budaya kekhasan dan orientasi individualistis dari oksidentalis telah merasuki profesi konseling. Baru-baru ini gelombang minat dalam spiritualitas dan agama telah dicatat dengan beberapa pelayanan yang terfokus pada pendekatan baru konseling. Pendekatan yang baru menunjukkan bahwa spiritualitas dalam kehidupan adalah pusat bagi individu, keluarga, dan komunitas. Terapis meneliti hubungan antara spiritualitas dan kesehatan psikologis umum. Para profesional sekuler dan religius mengakui terjadinya perubahan paradigma dari penyakit ke kesehatan dan dari individualisme ke kolektivisme. Penelitian ini mendasarkan pada kajian pustaka, dimana beberapa teori menyebutkan bahwa terdapat perspektif yang terintegrasi dengan pandangan konseling agama dan spiritualitas telah menghasilkan konflik mendasar dengan sistem nilai profesi yang berlaku. Konselor masih ingin menghindari peran sebagai seorang moralis. Kontroversi juga berkaitan dengan ketegasan yang diinginkan seseorang, terapis dalam melampirkan moral dan dimensi spiritual sambil menganjurkan nilai-nilai tertentu. Psikoterapi, sebagai  perusahaan moralistik, memerlukan modifikasi dalam program pelatihannya. Terapis perlu mengubah orientasi mereka, yakni sebagai ilmuwan dengan moral yang mendalam atau komitmen spiritual. Klien membutuhkan dan menuntut reorientasi seperti ini. Profesi ini memiliki klaim untuk menanggapi kebutuhan kliennya dan hal itu tidak bisa mengabaikan dorongan yang muncul dalam praktiknya.